Perawatan Dan Perbaikan Pada Pengelasan Teknologi Robotik Secara Preventive Maintenance Dengan Modulary Design - Hisyam; Muhamat Farisman; Jusman; Raden Rinova Sisworo; Aminur (Piston: Jurnal Teknologi, 2025)
The focus of this research was maintenance and repair of robotic welding technology using preventive maintenance with modular design. This concept organizes machine parts to reduce manufacturing costs, repair procedures, and reduce product defects, as well as minimize component damage such as undercut, overlap, and porosity. If component damage occurs, maintenance/replacement of components is not only carried out on the damaged component but also is connected to other components. The method used in this research was observation carried out by direct observation at the location of the information source at the company Showa Kinzoku.co.,ltd, as well as literature study in order to obtain complementary data and solve problems. This shows that there was a significant decrease in damage after research was carried out before maintenance was carried out in November {13.0}, December {12.3}, January {12.5}. After maintenance was carried out in February {4.12}, March {3.33}, April {3.76} the difference was very significant. In this research the author also looked at seasonal factors, in the winter in December product damage reached {12.5} damage and in the summer in April it decreased to {3.76} damage. Based on the results of the analysis, it can be concluded that the implementation of preventive maintenance with modular design is very effective, the January presentation data showed 77% damage, compared to April's only 23% damage. Maintenance significantly reduces average product defects by more than 50%, demonstrating high effectiveness in this period.